2021
DOI: 10.1161/jaha.120.020548
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of Inhaled Nitric Oxide on Right Ventricular Flow Hemodynamics by 4‐Dimensional–Flow Magnetic Resonance Imaging in Children With Pulmonary Arterial Hypertension

Abstract: Background Pulmonary arterial hypertension (PAH) manifests with progressive right ventricular (RV) dysfunction, which eventually impairs the left ventricular function. We hypothesized that 4‐dimensional–flow magnetic resonance imaging can detect flow hemodynamic changes associated with efficient intracardiac flow during noninvasive inhaled nitric oxide (iNO) challenge in children with PAH. Methods and Results Children with PAH (n=10) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…It is with this backdrop that Carter et al designed an MRI-compatible NO delivery device, which realized simultaneous NO inhalation and measurement of vasodilation [114]. Schafer et al further quantitatively investigated the correlation between inhaled NO and hemodynamic changes in intracardiac flow with four-dimensional-flow MRI [115]. They claimed that this method can link the quantity of delivered NO to the corresponding therapeutic effects, which may help the selection of the dose in clinical decision-making processes.…”
Section: The Inhaled Nitric Oxide Therapy To Treat the Pulmonary Hypertension And Coronavirus (Covid-19)mentioning
confidence: 99%
“…It is with this backdrop that Carter et al designed an MRI-compatible NO delivery device, which realized simultaneous NO inhalation and measurement of vasodilation [114]. Schafer et al further quantitatively investigated the correlation between inhaled NO and hemodynamic changes in intracardiac flow with four-dimensional-flow MRI [115]. They claimed that this method can link the quantity of delivered NO to the corresponding therapeutic effects, which may help the selection of the dose in clinical decision-making processes.…”
Section: The Inhaled Nitric Oxide Therapy To Treat the Pulmonary Hypertension And Coronavirus (Covid-19)mentioning
confidence: 99%
“…It is with this backdrop that, Carter et al designed a MRI-compatible NO delivery device, which realized the simultaneous nitric oxide inhalation and measurement of vasodilation [85]. Schafer et al further quantitatively investigated the correlation between the inhaled NO and hemodynamic changes in the intracardiac flow with four-dimensional-flow MRI [86]. They claimed that this method can link the quantity of delivered NO to the corresponding therapeutic effects, which may help the choice of dose in clinical decision-making.…”
Section: The Inhaled Nitric Oxide Therapy To Treat the Pulmonary Hypertension And Coronavirus (Covid-19)mentioning
confidence: 99%
“…Several groups of authors reported on changes and inefficient blood flow propagation in the ventricles of patients with ischemic heart disease and dilated cardiomyopathy 3,4 . Furthermore, alternations of flow were found in both ventricles of children with pulmonary artery hypertension (PAH), whilst a significant response was recorded in the right ventricle (RV) after inhaled nitric oxide challenge 5 . Patients with PAH presented with increased RV dimensions, increased RV residual volumes, and decreased direct RV inflow and RV systolic function 5 .…”
mentioning
confidence: 99%
“…3,4 Furthermore, alternations of flow were found in both ventricles of children with pulmonary artery hypertension (PAH), whilst a significant response was recorded in the right ventricle (RV) after inhaled nitric oxide challenge. 5 Patients with PAH presented with increased RV dimensions, increased RV residual volumes, and decreased direct RV inflow and RV systolic function. 5 François et al analyzed 4D MRI velocity mapping in patients with repaired tetralogy of Fallot vs. controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation